MODEL DEVELOPMENT PHARMACEUTICAL CONSULTATION FOR EVALUATION AND MONITORING TYPE 2 DIABETIC PATIENTS - Arnaldo Zubioli; Maria Angélica R. C. P. da Silva; Raquel S. Tasca; Roberto B. Bazotte (Formifarma, LDA., 2012)
Objectives: The purposes of this study were the development and evaluation of a pharmaceutical consultation (PC) program to reduce the risks of chronic complications in type 2 diabetic patients (T2DP). Methods: T2DP receiving conventional medical treatment but showing ineffective glicemic control (fasting glycemia > 140 mg/dl and/or glycated hemoglobin > 7) were selected among patients from the Pharmacy School or popular pharmacy of State University of Maringá (Paraná state, Brazil). The PC evaluated drug therapy and its monitoring through the clinical laboratory parameters, vital signs and anthropometry. The PC was repeated every 4 months during 1 year. The PC includes strategies that have been used successfully in other pharmaceutical care models, namely Dader's method, SOAP's (Subjective data, Objective data, Assessment, and Plan of care) method, Pharmacist´s Workup of Drug Therapy (PWT) method and models of nurse care used in Brazil. Results: Fifty patients completed the study (1 year). There was a reduction of glycemia (P<0.0001), glycated hemoglobin (P = 0.0022), total cholesterol (P = 0.0072), triacylglycerol (P = 0.0204), systolic blood pressure (P<0.0001), diastolic blood pressure (P<0.0001) and elevation of low density lipoprotein (p = 0.0042). The pharmacological profile and therapeutic schedule of drugs consumption after starting (0 month) and finish (12 months) the study were very similar. For this reason the increased concordance with drug treatment and the pharmacological correction of drug-related problems contributed to improve the medical treatment of diabetes. Conclusions: The PC program developed in this study was suitable to promote reduction of chronic complications risk factors in T2DP.